Prevalence and antimicrobial resistance of shiga toxin-producing Escherichia coli and enteropathogenic Escherichia coli isolated from patients with acute diarrhea - Bouzari, Saeid (Iran J Microbiol, 2018)
BACKGROUND AND OBJECTIVES: Diarrheal disease is still a major health problem in developing countries, where it is considered as one of the leading causes of morbidity and mortality especially in children. Escherichia coli is one of the important enteropathogenic bacteria which causes diarrhea in people. The aim of this study was to investigate the prevalence and antimicrobial resistance of shiga toxin–producing E. coli (STEC), Enterohaemorrhagic E. coli (EHEC), and Enteropathogenic E. coli (EPEC) in fecal samples collected from patients with acute diarrhea in a number of Iranian provinces. MATERIALS AND METHODS: A total of 102 strains of E. coli were isolated from fecal samples collected from patients with acute diarrhea using microbiological phenotypic tests. The antibiotic susceptibility pattern of all isolates was determined by the disk agar diffusion (DAD) method. The presence of eae, bfp, stx1, sts2 and EAF genes in the isolates was investigated by PCR. The results were analyzed by SPSS; version 17.0 software. RESULTS: Out of 102 E. coli isolates screened for specific genes, 52 strains of E. coli were identified to harbor STEC 26 (50%), EPEC 13 (25%) and EHEC 13 (25%). Greatest resistance was observed to amoxicillin and ampicillin 40 (76.9%), and most sensitivity to imipenem 52 (100%) and gentamicin 40 (76.9%). We also found that 80.77% of diarrheic E. coli isolates were multidrug resistant (MDR). CONCLUSION: The results showed that E. coli is one of the major causes of diarrhea and is highly resistant to commonly used antibiotics; therefore, officials must pay great attention to this issue in order to increase the health of the community.